Does a Bachelor's degree pay off? Labor market outcomes of academic versus vocational education after Bologna - Martin Neugebauer; Felix Weiss (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
Academic education is generally rewarded by employers, but what happens to graduates if they are trained for two years less and have to compete with vocationally trained labor market entrants in a similar field of study? Focusing on Germany, we analyze labor market entries of individuals eligible for higher education, who either opted for newly introduced short bachelor's degrees, or for well-established vocational degrees. Based on Microcensus data, we find that bachelor's degrees from classical universities are associated with higher earnings and more prestigious jobs than initial vocational training degrees, and with higher prestige (but similar earnings) than further vocational degrees. However, bachelor's degrees from universities are also related to higher risks of unemployment or fixed-term employment. Universities of applied sciences, which combine academic and practical training, offer both high earnings and prestigious jobs as well as low risks of unemployment or fixed-term employment at the bachelor's and the master's level. Overall, 'general' academic education provides advantages over vocational education, despite these structural changes. Variations by field of study are reported.
Keywords: I26; I23; J24; J31; 330; labor market outcomes; Bologna Process; vocational education; higher education; Germany